Live Streaming Synchronization Using Event-Triggered Consensus Control - Gioacchino Manfredi; Vito Racanelli; Luca De Cicco; Saverio Mascolo (IEEE Transactions on Control of Network Systems, 2025)
The advent of social media applications and mobile devices has allowed users to experience live streaming events (e.g., a football match) together, even if they are not in the same physical place. However, this service brings along the issue of ensuring a synchronized video playback among geographically distributed users. Users leave comments and reactions to an online live event on social networks. As a consequence, an unsynchronized video playback can be easily noticed and be detrimental to users’ feelings of togetherness. In this work, we propose a distributed control approach to achieve synchronization among users. In particular, the well-known consensus problem of first-order integrators with saturated inputs is employed to design a distributed playback synchronization framework. Furthermore, we propose a leader–follower approach to ensure a controlled synchronization among users in order to obtain the least possible delay with respect to the video content provider. Finally, an event-triggered control is introduced as an enhancement to the previously developed control with the aim of reducing the information exchanged among users. Simulations on different network topologies confirm that the proposed approach is effective at enforcing asymptotic synchronization.
Keywords: Streaming media; Synchronization; Bandwidth; Quality of experience; Event detection; Bit rate; Media; Encoding; Adaptive systems; Sports; Consensus; event-triggered control; multiagent systems; video streaming